Teachers' coping styles and factors inhibiting teachers' preferred classroom management practice. (May 2015) - Salkovsky, Merav; Romi, Shlomo; Lewis, Ramon (Rom)
Abstract: The relationship between 294 teachers' coping styles and factors they perceive as inhibiting them from using their ideal classroom management is investigated. The results show that a coping style that includes strategies such as self-blame and wishful thinking relates to greater identification of both personal inhibitory factors (e.g., time and work demands), and broader factors (e.g., accountability to parents). Conversely, a coping style incorporating physical activity and a focus on the positive, relates negatively to personal inhibitory factors. Somewhat surprisingly, teachers' use of socially embedded problem solving failed to relate to the perceived prominence of inhibitors to preferred management practice. Highlights: Five factors inhibit teachers from applying their preferred classroom management. Non-productive coping relates to more awareness of two types of inhibitors. Productive coping relates to less awareness of personal inhibitors (e.g. no time). Problem solving does not relate to awareness of any of the inhibitors.